Use of physiotherapy resources for patients with fibromyalgia - Nóbrega, Antonio José Sarmento da; Barros, Maria de Fátima Alcântara; Carvalho, Antonio Geraldo Cidrão de; Araújo, Maria das Graças Rodrigues Araújo; Lucena, Neide Maria Gomes de (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Fibromyalgia is a non-inflammatory rheumatic syndrome of unknown etiology manifested in the musculoskeletal system through diffuse and chronic pain and presence of tender points, which may be associated with fatigue, anxiety, muscle stiffness, skin sensitivity, pain after exercise, functional impairment and sleep disorders. Objective: This study aimed to perform a systematic literature review in order to check which physiotherapy resources are mostly used today and what are the most significant results in the treatment of fibromyalgia. Method: An integrative literature review was conducted by searching electronic databases of indexed data such as Latin American and Caribbean Health Sciences (LILACS), MEDLINE/ PubMed and Scientific Electronic Library Online (SCIELO). Randomized clinical trials were selected in the period from January 2001 to June 2013 published in Portuguese, English and Spanish. Methodological quality was assessed using the Jadad Quality Scale. Results: Overall, 522 studies were reviewed in full and only 13 were included after application of the exclusion criteria. Among these, articles that addressed the use of electrotherapic resources (n = 4), hydrotherapy (n = 3), conventional therapy (n = 3), physical exercise (n = 2) and multidisciplinary treatment (n = 1) were identified, with diversified results, protocols and application times of each methodology. Conclusion: It has been found that there are a small number of studies with scientific relevance published in the last 10 years evidencing techniques that have obtained better results in the treatment of patients with fibromyalgia. Further studies with better design aimed at obtaining more conclusive results should be conducted.